2015
DOI: 10.1021/acs.jctc.5b00414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CM5 Charges for Nonaqueous Condensed-Phase Modeling

Abstract: Partial atomic charges for neutral molecules from quantum mechanical calculations are typically scaled for use in molecular modeling of liquid-phase systems. Optimal scale factors of 1.14 for CM1A and 1.27 for CM5 charges were previously determined for minimizing errors in free energies of hydration. The adequacy of the 1.14*CM1A and 1.27*CM5 models are evaluated here in pure liquid simulations in combination with the OPLS-AA force field. For 22 organic liquids, the 1.14*CM1A and 1.27*CM5 models yield mean uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 60 publications
4
105
0
1
Order By: Relevance
“…In addition, it makes computed ΔG hyd values too positive with a Mean Signed Deviation (MSD; experiment - calculated) of −1.14 kcal/mol; however, use of a larger scale factor with CM5 would lead to poorer results for liquid densities and heats of vaporization. 29,30 The other advantage of correcting the CM1A rather than CM5 charges is the relative simplicity of the underlying AM1 calculations for the former.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it makes computed ΔG hyd values too positive with a Mean Signed Deviation (MSD; experiment - calculated) of −1.14 kcal/mol; however, use of a larger scale factor with CM5 would lead to poorer results for liquid densities and heats of vaporization. 29,30 The other advantage of correcting the CM1A rather than CM5 charges is the relative simplicity of the underlying AM1 calculations for the former.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that use of only 19 LBCC was able to lower the MAD for the 426 free energies of hydration to 0.61 kcal/mol. Further improvements are expected to be limited by the accuracy of the experimental data 30 and the simplicity of the atom-centered point charge model. The 1.14*CM1A-LBCC charges in conjunction with the OPLS-AA force field were also tested for calculating heats of vaporization ( ΔH vap ) and densities of ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modulation involves a 20 % magnification of the AM1-BCC partial charges and a corresponding linear inflation of the Lennard–Jones parameters to maintain the proper liquid densities with the increased charge magnitudes. This degree of charge magnitude amplification has been seen as beneficial for neat liquid and molecular transfer properties by our group and others [15, 25], while the linear inflation is derived from automated dielectric optimization of small molecule functional groups. Here, the modulation amounts to a generally applied percent inflation for each atom of the molecule.…”
Section: Methodsmentioning
confidence: 99%
“…Hitalictot=HintraAA+HinterAA+HintraCG+HinterCG+HinterCG/AA. parameters of the OPLS-AA force field 25,26 with 1.14*CM1A 31,32 or 1.20*CM5 28,33,34 partial atomic charges were used to describe solute interactions. Martini force field 2.0 35 and the polarizable Martini CG water model 27 were used for intra- and inter-molecular CG interactions.…”
Section: Computational Detailsmentioning
confidence: 99%